A comparison of blood loss and the need for transfusion following primary total knee replacement with or without the use of a tourniquet - Kirmani, Sayyied J.; Middleton, Mark; Fontalis, Andreas; Srivastava, Raka; Dinah, Feroz (International Journal of Research in Orthopaedics, 2018)
Background: Primary total knee replacement (TKR) has traditionally been carried out with the use of a tourniquet. More recent trends towards performing the surgery without a tourniquet have had some support in the literature and may improve patient recovery. Methods: A retrospective cohort of 198 consecutive primary TKRs from our institution were identified and analysed, 52 used a tourniquet and 146 did not. All TKRs also utilised a standardised interventions protocol including withholding of anticoagulants and antiplatelet medications, topical adrenaline injection, and both IV and topical tranexamic acid. Outcomes measured were estimated intra-operative blood loss, overall blood loss through comparison of pre and post-operative haemoglobin laboratory values, and the need for post-operative blood transfusion. Results: Analysis demonstrated a statistically significant reduction in estimated intra-operative blood loss when a tourniquet was used (p<0.001). However, overall blood loss indicated by the haemoglobin drop after surgery was not significantly affected by tourniquet use (p=0.342). Transfusion requirements were also similar among the groups (4.8% vs. 5.8%) and no tendency was suggested towards an increased rate of transfusion in the non-tourniquet group. Conclusions: Our study shows that although estimated intra-operative blood loss is increased without a tourniquet, total blood loss as measured by haemoglobin levels is no different for primary TKRs that use a tourniquet and those that do not. Furthermore there is no difference in post-operative blood transfusion rates. It is our hope that this study will add to the body of evidence for surgeons to consider no longer using a tourniquet for primary TKR.